Practical Control for Two-Mass Positioning Systems in Presence of Saturation - Fitri Yakub; Andika Aji Wijaya; Mustafa Al-ani (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
The precision positioning systems generally need a good controller to achieve a fast response, high accuracy and robustness. In addition, ease, simplicity of controller design structure and high motion control performance are very important for practical applications. For satisfying these requirements, nominal characteristic trajectory (NCT) with proportional integral (PI) and notch filter (NF) as a compensator has been proposed as a practical control method for two-mass rotary PTP positioning systems. However, the effect of the actuator saturation cannot be completely compensated due to integrator windup when the object parameter varies. This paper presents a method to further improve nominal characteristic trajectory following (NCTF) controller to overcome the problem of integrator windup by adopting PI anti-windup schemes. The improved NCTF controller is evaluated experimentally using two-mass rotary positioning systems. The effect of the design parameters on the robustness of the improved NCTF with anti-windup integrator controller is evaluated and compared with NCTF without anti-windup integrator and the equivalent PID controller. The results show that the improved NCTF controller is effective to compensate the effect of integrator windup.